GUIDELINES TO PROMOTE RESOURCE SHARING MANAGEMENT IN UNIVERSITIES IN THE DATA ERA - Junqing, Tang; Suteeniran, Niran; Dejhome, Pachara; Kaewsrimon, Buranajit; Wimuttipanya, Jittawisut (Journal of MCU Nakhondhat, 2024)
The objectives of this research are to 1) analyze the current situation and current problems of university resource sharing in the information age and 2) comprehensively evaluate the effectiveness of university resource sharing in the information age. This research is a mixed methods research. The research tools used were estimation questionnaires. It has a reliability value of .93, divided into 6 areas, consisting of 1) human resources, 2) financial resources, 3) material, equipment, and building resources, 4) management resources, 5) time resources, 6) information technology resources. The population includes 200 teachers, students, and personnel involved in university resource management in Yunnan Province. Data analysis was performed using percentages, means, and standard deviations. and content analysis The results of the research found that 1) Current probl ems in resource sharing in universities in the information age include knowledge and understanding of personnel. contribution Management innovation Management system and efficiency evaluation for development and improvement, and 2) the overall evaluation results were at the highest level (μ = 4.55, σ = 1.71). When considering each aspect, it was found that the highest were information technology resources, followed by information resources. person Administrative resources Resources in materials, equipment, and buildings Financial resources and the least are time resources, respectively. And should promote the management of university resources in the information age, especially in the digital age, which brings innovations to organizational management and the creation of strategies for the development of effectiveness and efficiency. of organizational goals to have standards By promoting the participation of everyone in the organization through information technology systems and data management towards excellence.